Nanoplastics transport to the remote, high-altitude Alps. (1st November 2021) - Materić, Dušan; Ludewig, Elke; Brunner, Dominik; Röckmann, Thomas; Holzinger, Rupert
Abstract: Plastic materials are increasingly produced worldwide with a total estimated production of >8300 million tonnes to date, of which 60% was discarded. In the environment, plastics fragment into smaller particles, e.g. microplastics (size < 5 mm), and further weathering leads to the formation of functionally different contaminants – nanoplastics (size <1 μm). Nanoplastics are believed to have entirely different physical (e.g. transport), chemical (e.g. functional groups at the surface) and biological (passing the cell membrane, toxicity) properties compared to the micro- and macroplastics, yet, their measurement in the environmental samples is seldom available. Here, we present measurements of nanoplastics mass concentration and calculated the deposition at the pristine high-altitude Alpine Sonnblick observatory (3106 MASL), during the 1.5 month campaigh in late winter 2017. The average nanoplastics concentration was 46.5 ng/mL of melted surface snow. The main polymer types of nanoplastics observed for this site were polypropylene (PP) and polyethylene terephthalate (PET). We measured significantly higher concentrations in the dry sampling periods for PET (p < 0.002) but not for PP, which indicates that dry deposition may be the preferential pathway for PET leading to a gradual accumulation on the snow surfaces during dry periods. Air transport modelling indicates regional and long-range transport of nanoplastics, originating preferentially from European urban areas. The mean deposition rate was 42 (+32/-25) kg km −2 year −1 . Thus more than 2 × 10 11 nanoplastics particles are deposited per square meter of surface snow each week of the observed period, even at this remote location, which raises significant toxicological concerns. Graphical abstract: Image 1 Highlights: We detected nanoplastics of different types at a remote high-altitude site. The average nanoplastics concentration was 46 ng/mL of melted surface snow. The calculated deposition rate at the snow surface was 42 kg km −2 year −1 . Urban areas in western Europe are important sources of nanoplastics at this site.